2013
DOI: 10.1371/journal.pone.0071864
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Expression of C-X-C Chemokine Receptor 4 Is an Independent Prognostic Predictor for Patients with Gastric Cancer

Abstract: Aberrant chemokine (C-X-C motif) receptor CXCR4 expressions in malignant tissues have been reported, but its role in gastric cancer prognosis remains unknown. Our studies were designed to investigate the expression and prognostic significance of CXCR4 in patients with gastric cancer. CXCR4 expression was retrospectively analyzed by immunohistochemistry in 97 patients with gastric adenocarcinoma from China. Results were assessed for association with clinical features and overall survival by using Kaplan-Meier a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
1
28
1
Order By: Relevance
“…CXCL12 expression is an independent prognostic factor for aggressive phenotypes of GC, including tumor size, invasion depth, lymphatic invasion and metastasis, TNM staging, surgical outcome, and the OS . The intensity of CXCR4 in primary GC lesion is positively associated with TNM staging, LN involvement, and recurrence/metastasis rate after radical surgery, but negatively with OS and disease‐free survival (DFS) . As for the combination of CXCR4 and CXCL12 levels, CXCR4 high /CXCL12 high in GC is significantly associated with tumor invasion depth, LN involvement, and higher TNM stage, which causes the worst prognosis, whereas patients with CXCR4 low /CXCL12 low show the best prognosis .…”
Section: Expression Of Cxcl12/cxcr4 Axis In Gcmentioning
confidence: 99%
“…CXCL12 expression is an independent prognostic factor for aggressive phenotypes of GC, including tumor size, invasion depth, lymphatic invasion and metastasis, TNM staging, surgical outcome, and the OS . The intensity of CXCR4 in primary GC lesion is positively associated with TNM staging, LN involvement, and recurrence/metastasis rate after radical surgery, but negatively with OS and disease‐free survival (DFS) . As for the combination of CXCR4 and CXCL12 levels, CXCR4 high /CXCL12 high in GC is significantly associated with tumor invasion depth, LN involvement, and higher TNM stage, which causes the worst prognosis, whereas patients with CXCR4 low /CXCL12 low show the best prognosis .…”
Section: Expression Of Cxcl12/cxcr4 Axis In Gcmentioning
confidence: 99%
“…The tissue microarray and immunohistochemistry protocols were constructed as described previously [25,26]. Primary antibodies were against CD68 (Dako, Glostrup, Denmark), CD11c (Abcam, Cambridge, MA, USA), and CD206 (Abcam, Cambridge, MA, USA).…”
Section: Patients and Specimensmentioning
confidence: 99%
“…Despite recent advances in treatment, the prognosis of patients with cancers in digestive system remains poor. Numerous studies have reported molecular predictors of prognosis of patients with digestive system cancers . However, no specific molecular biomarker of this kind has been accepted commonly and used routinely until now.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported molecular predictors of prognosis of patients with digestive system cancers. [2][3][4][5] However, no specific molecular biomarker of this kind has been accepted commonly and used routinely until now. Clinically applicable biomarkers for prognosis analysis are urgently required.…”
Section: Introductionmentioning
confidence: 99%